Tourism Promotion Strategies Based On Digital Tourism On Social Media Instagram By The Youth Tourism And Sports Agency In The Pesisir Selatan District: Strategi Promosi Pariwisata Berbasis Digital Tourism Pada Media Sosial Instagram Oleh Dinas Pariwisata Pemuda Dan Olahraga Di Kabupaten Pesisir Selatan - Syofira Mayang Sari; Aldri Frinaldi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Digital tourism or e-tourism is an integration between ICT development and the tourism industry. The phenomenon in the field shows that the Digital Tourism-Based Tourism Promotion Strategy on Instagram Social Media by the Tourism, Youth and Sports Office in South Pesisir Regency varies greatly. The purpose of this study was to analyze the promotion strategy, obstacles, and efforts to overcome obstacles in the Digital Tourism-Based Tourism strategy on Instagram Social Media by the Tourism, Youth and Sports Office in South Pesisir Regency. Qualitative research is used in this type of research. This research was conducted at the South Pesisir Regency Youth and Sports Tourism Office. The data collection techniques and tools were carried out by means of observation, interviews and documentation studies. In this study using the Miles and Huberman version of data analysis, that there are three lines of activity, namely data reduction, data presentation, and conclusion drawing or verification. From the description and analysis of the data, it can be concluded that overall the tourism promotion efforts made by the Tourism, Youth and Sports Office through the Instagram platform have not been optimal.